O ensino interdisciplinar de Física no Ensino Médio sobre os efeitos da utilização do protetor solar na exposição à radiação ultravioleta através da modelagem matemática - QUEIROZ, Suzely Trindade (2021)
This work aimed to implement a methodological strategy based on interdisciplinarity in the teaching of physics. The classes took place remotely using digital information and communication technologies (TDIC) and mathematical modeling based on the 3 acts of Dan Meyer. The application was carried out with 64 third-year high school students in a public school located in the city of Belém-PA. The meetings took place through the google meet platform with the theme: The effects of using sunscreen on exposure to ultraviolet radiation. Data collection was recorded through the participation of students in interactive activities on the Mentimeter platform, and with works made in asynchronous classes, it was also possible to observe such a situation involving students with low vision, in this case it was necessary to make changes in the material used for promote inclusion. This work, therefore, seeks to present a perspective of teaching physics when integrated with other areas of knowledge.